MENINGKATKAN HASIL BELAJAR SISWA MENGGUNAKAN MEDIA BOLA DENGAN TEKNIK LAY UP SHOOT PADA MATERI SURAT LAMARAN PEKERJAAN - Fatimah, Siti (Universitas Islam Zainul Hasan Genggong, 2023)
A lay up shoot is a shot that is taken at very close range to the basketball hoop, so that it is as if the ball is being placed into the basketball hoop which is preceded by a two step movement, ball media using the lay up shoot technique is able to improve student learning outcomes in in class because it makes students happy with the method used, teaching and learning in class using the lecture method alone often makes students bored and not infrequently some of them are sleepy, this means that the material delivered by the teacher cannot be fully absorbed by the participants. students which will ultimately result in the learning objectives not being achieved. This research was conducted to determine the effectiveness of using football media using the Lay Up Shoot technique in job application letter material in class XII, precisely at MA WALISONGO. The use of ball media using the Lay Up Shoot technique is carried out in class involving the teacher and all students. In addition to achieving learning objectives, this method is intended for students to concentrate. Using this method also makes the material easier to understand and learning in class more enjoyable.